Body composition and handgrip strength in patients with prediabetes: A case-control study from Haryana, North India. Issue 3 (May 2021) - Rajput, Rajesh; Garg, Rakesh; Rajput, Meena; Rani, Monu; Darshan An, Venkatesh
Abstract: Background and aims: Previous studies suggest that body composition and handgrip strength are significantly altered in individuals with type 2 diabetes mellitus. Only few studies are available in prediabetic individuals. The aim is to study the change in body composition in adult individuals with prediabetes and compare it with age and sex-matched normoglycemic individuals. Methods: 100 diagnosed cases of prediabetes and 100 age and sex-matched normoglycemic controls were recruited in the study. Body composition was assessed with Omron HBF 510w and Slim guide skinfold caliper. Handgrip strength was assessed with Camry digital dynamometer. Results: Out of 100 subjects with prediabetes; 53 were female and 47 were male. In this study, there was higher mean body fat percentage (29.37 ± 5.65 vs 25.46 ± 5.27) and visceral fat (11.21 ± 1.92 vs 7.27 ± 2.82) in individuals with prediabetes compared to normoglycemic individuals. Also, there was a lower mean of skeletal muscle percentage (27.21 ± 4.32 vs 31.19 ± 4.63) and handgrip strength (29.61 ± 6.38 vs 33.75 ± 6.8) in individuals with prediabetes compared to normoglycemic individuals. In this study, body fat percentage was positively correlated (r = 0.3385) with prediabetes. The skeletal muscle percentage (r = −0.40721) and handgrip strength (r = −0.301) were negatively correlated with prediabetes. Conclusions: It can be concluded that there is a significant change in body composition and handgrip strength in the individuals with prediabetes, and changes in body composition and handgrip strength can be included as a primary care strategy to motivate lifestyle modifications. Highlights: Body composition and handgrip strength are altered in diabetic individuals. This association less studied in prediabetic individuals. Significant alteration of body composition seen in prediabetic individuals. Lower handgrip strength seen in prediabetic individuals.